(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this study Rossby waves dispersion was developed by using Rossby wave equation has been shown That the normal waveform for the Rossaby waves in the plane a circle in the wave form space. its center is displaced by a unit along the negative X-axis and a radius smaller than this displacement .the phase propagation is initially west ward ,while the phase speed scheme is a circle centered Dislikes by amount only by negative X-axis ,the group speed chart is ellipse its center is shifted to the west , The main and sub-axes give the whole group a great speed as a function of frequency and Mediator .